IMPLEMENTASI KEBIJAKAN PERATURAN WALI KOTA SEMARANG NOMOR 12 TAHUN 2023 TENTANG PEMBENTUKAN, KEDUDUKAN, SUSUNAN ORGANISASI, TUGAS DAN FUNGSI SERTA SISTEM KERJA UNIT PELAKSANA TEKNIS DINAS AMONG JIWO PADA DINAS SOSIAL KOTA SEMARANG (KAJIAN PASAL 5 TENTANG TUGAS UPTD AMONG JIWO) - Qorina Hasna; Sri Suwitri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
UPTD Among Jiwo is a Technical Implementation Unit under the Semarang City Social Affairs Office is mandated to provide basic services for beneficiaries temporarily accommodated. Field demands that frequently exceed formal capacity, along with misperceptions regarding the institutional status of UPTD Among Jiwo, often create discrepancies in service expectations among external stakeholders. This study aims to analyze the implementation of planning, coordination, fostering, and supervision functions in delivering basic services and to identify factors influencing their implementation. The research employs a qualitative descriptive method using interviews, observation, and documentation. The analytical framework is based on George C. Edwards III’s policy implementation model and Van Meter and Van Horn’s perspective. The findings indicate that the implementation of duties has been carried out, however, it remains constrained by limited resources, the need for professional social workers (peksos) and social counsellors (pensos), and external environmental factors such as quota limitations and rigid eligibility requirements of provincial social institutions. Supporting factors include consistent internal communication and responsive, adaptive implementer disposition. The study recommends strengthening resources and enhancing operational budget utilization.